1988
DOI: 10.1172/jci113722
|View full text |Cite
|
Sign up to set email alerts
|

Gamma heavy chain disease in man. Genomic sequence reveals two noncontiguous deletions in a single gene.

Abstract: A genomic clone was isolated from a human lymphoid cell line which synthesized an NHrterminally deleted gamma3 heavy chain disease protein. Nucleotide sequence analysis revealed a normal sequence from 310 bp 5' to the initiator ATG through the codon for VH amino acid 14. Amino acid 15 was derived from the codon for the last J4 amino acid. Thus, the clone contained a deletion of the codons for the VH region beyond amino acid 14, as well as those for the entire D region and most of the J coding region. Some sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…In all gamma-HCD proteins, the entire C H I domain is also deleted, with the normal sequence beginning at the hinge or occasionally at the C H 2 domain. 8,9 Gamma-HCD can be divided into two categories: lymphoproliferative (disseminated or localized) and not associated with any lymphoproliferative disease. 2 Our patient presented with lymphadenopathies and splenomegaly and would therefore be included in the first group.…”
Section: Discussionmentioning
confidence: 99%
“…In all gamma-HCD proteins, the entire C H I domain is also deleted, with the normal sequence beginning at the hinge or occasionally at the C H 2 domain. 8,9 Gamma-HCD can be divided into two categories: lymphoproliferative (disseminated or localized) and not associated with any lymphoproliferative disease. 2 Our patient presented with lymphadenopathies and splenomegaly and would therefore be included in the first group.…”
Section: Discussionmentioning
confidence: 99%
“…Positive clones were obtained by screening 5 x 105 recombinants with a C>y3 cDNA probe (17), which is known to cross hybridize to all C-y genes (18). A second genomic library constructed from EBVtransformed B-lymphocytes was screened to obtain the normal chromosome 11 clone, using a chromosome 11-specific p1lHHO.5 probe (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…[15] that showed rearrangement of an immunoglobulin -y heavy chain constant region gene (C0y). Cloning was accomplished using a C-y cDNA probe (17) to screen a somatic cell hybrid genomic library containing the human 14q + derivative chromosome of the translocation t (11;14). A C&y-positive clone X14q+4 was isolated ( Figure 1) Figure 2A).…”
Section: Methodsmentioning
confidence: 99%
“…In the previously reported case of patient OMM with ␥3 heavy-chain disease (2,(7)(8)(9), the deleted ␥3 protein present in serum started at the N-terminus of the hinge region (residue 226 in normal ␥3), whereas the complementary DNA (cDNA) and protein product of cloned cells, as well as that translated from the respective messenger RNA, showed that an additional segment consisting of the 14 N-terminal amino acid residues of V H plus a proline at position 15 was directly attached to the hinge. This apparent discrepancy was apparently caused by posttranslational proteolysis.…”
mentioning
confidence: 94%
“…Heavy-chain disease is a lymphoproliferative disorder characterized by production of monoclonal Ig heavy chains of smaller size than their normal counterparts and with no covalently linked light chains (1)(2)(3). The disease is clinically quite heterogeneous (4), and some patients show manifestations caused by deposition of the abnormal, monoclonal heavy chain in various tissues, with ensuing organ damage and dysfunctionso-called heavy-chain deposition disease (HCDD) (3,5).…”
mentioning
confidence: 99%